Training Model to Enhance Human Resource Development of Government Organizations - Kerdnoonwong, Sumolnit (International Journal of Engineering and Technology, 2018)
The research was aimed to (1) study the best practices of the organizations that have been awarded the Public Sector Management Quality Award (PMQA) (2) present the recommendations of the training model that promote human resource development of government organizations in Thailand. The study was found that the Department of Community Development and the Department of Mental Health were only two organizations that have been awarded PMQA in the sector of staff administration and development. They had similar policy on staff administration and development which was focused on the development of personnel as "human capital" as well as “training” is one of the most important tools in order to develop the staff. The concept of training was based on the criteria of OPDC (Office of the Public Sector Development Commission), position competency, well-being and satisfaction of the staff. Training process step starts from need analysis, then develop courses and assess of the training. The training methods are both formal and informal training which is based on the context the content of the training, the trainee the time and place. Quality assurance system, follow-up evaluation by trainees and their supervisors are the training management.
Keywords: Human Resource Development; Lifelong Education; Organization Administration; Training